2011
DOI: 10.1118/1.3641644
|View full text |Cite
|
Sign up to set email alerts
|

Application of the gamma evaluation method in Gamma Knife film dosimetry

Abstract: The gamma evaluation method was applicable to GK radiosurgery. For all test plans, planning dose distribution and film measurement met the tolerance criteria of 0.5 mm∕0.5% within the 50% isodose line which are used for marginal dose prescription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…The calibration procedure was followed as mentioned in Jeong-Hoon Park et al (Park et al, 2011). The films for calibration, treatment verification and radiological precision were scanned with similar procedure.…”
Section: Film Scanning For 2d Verificationmentioning
confidence: 99%
“…The calibration procedure was followed as mentioned in Jeong-Hoon Park et al (Park et al, 2011). The films for calibration, treatment verification and radiological precision were scanned with similar procedure.…”
Section: Film Scanning For 2d Verificationmentioning
confidence: 99%
“…The relative dose distribution in the plane perpendicular to the beam path is obtained using predetermined Monte‐Carlo (MC) simulation results. The relative dose distributions of a GK have been verified in many reports using film dosimetry or independent MC simulations . However, these verifications only employed relative comparison methods in one dimension or qualitative verification with two‐dimensional lines instead of analytic quantitative verification, with the exception of Park et al.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] In recent times radiochromic films have been accepted as dosimetric tools in GK. [7][8][9]4,6 Yamauchi et al showed a comparison of absolute linear dose profiles in the head phantom with TPS data for four collimators of GK using Gafchromic TM (International Specialty Products, Wayne, NJ) MD-55 films and a flatbed scanner. 9 Novotny et al 8 measured relative output factors for small collimators of GK Perfexion via absolute film dosimetry using Gafchromic EDR2, EBT, and MD-55 films.…”
Section: Introductionmentioning
confidence: 99%
“…5 In one of our previous studies, we have shown a verification method for shield based planning using EBT2 film and gel dosimetry. 4 In a recent work by Park et al, Gamma evaluation method using Gafchromic EBT2 film for verification of GKSRS was done. 10,4 This was possible due to the direct acquisition of calculated TPS dose distribution for comparison.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation